2018
DOI: 10.1089/end.2017.0700
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Holmium Laser Enucleation and Plasmakinetic Resection of Prostate: A Randomized Trial with 72-Month Follow-Up

Abstract: The long-term follow-up data of this randomized trial confirm that HoLEP and PKRP are both effective and durable surgical interventions for the treatment of lower urinary tract symptoms due to BPE. Given the clinically relevant advantages associated with HoLEP, the alternation of PSA level, sexual function, and urination can be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Four studies reported the frequency of RE after EEP and TURP, one at month 3 23 and three at month 24. 19,20,27 As shown in the forest plot ( Fig. 6), no significant difference in RE was found between EEP and TURP (RR = 1.02, 95% CI: 0.85-1.23).…”
Section: Sexual Functionmentioning
confidence: 83%
See 3 more Smart Citations
“…Four studies reported the frequency of RE after EEP and TURP, one at month 3 23 and three at month 24. 19,20,27 As shown in the forest plot ( Fig. 6), no significant difference in RE was found between EEP and TURP (RR = 1.02, 95% CI: 0.85-1.23).…”
Section: Sexual Functionmentioning
confidence: 83%
“…Database searching yielded a total of 415 references, including 13 unpublished studies from Clinical-Trials.gov. After abstract screening and full-text review, 10 eligible studies were included for final analysis, [18][19][20][21][22][23][24][25][26][27] contributing a total sample size of 1435 patients. A summary of the characteristics of each included study is presented in Table 1.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study that compared TURP and HoLEP, assigned patients to three groups according to prostate sizes and, concerning operation length, TURP length was shorter in the 40 gr and 40-80 gr groups, and operation length was the same in the >80 gr group [21]. Gu M et al [22] compared 72-month follow-up outcomes of plasmakinetic prostate resection and HoLEP in 280 patients and found that Qmax, decrease in PSA level, International Index of Erectile Function (IIEF) score, and need for retreatment was found in favor in HoLEP. Woo MJ et al [23] compared results of TURP and HoLEP in 56 patients and six-month postoperative tests were in favor of HoLEP according to Qmax and post-void residual volume (PVR).…”
Section: Discussionmentioning
confidence: 99%